A Systematic Evaluation of ADHD and Comorbid Psychopathology in a Population-Based Twin Sample - Volk, Heather E; Neuman, Rosalind J; Todd, Richard D (Journal of the American Academy of Child and Adolescent Psychiatry, 2005)
Objective: Clinical and population samples demonstrate that attention-deficit/hyperactivity disorder (ADHD) occurs with other disorders. Comorbid disorder clustering within ADHD subtypes is not well studied. Method: Latent class analysis (LCA) examined the co-occurrence of DSM-IV ADHD, oppositional defiant disorder (ODD), conduct disorder (CD), and depression symptoms in a population twin sample. The authors fit separate models for ADHD and comorbid disorder symptoms. Twin concordance ratios (monozygotic versus dizygotic) were compared examining genetic influence on class membership. Results: LCA of ADHD symptoms resulted in seven classes including inattentive, combined, and hyperactive subtypes in 1,616 subjects. The few ADHD symptoms (53.4%) and severe inattentive (12.3%) classes were most frequent. LCA of ODD, CD, and depression symptoms in 1,587 subjects revealed five classes including ODD (19.4%), depression (14.5%), and two composite classes: ODD/CD (6.9%) and ODD/CD/depression (7.2%). Internalizing and externalizing comorbid disorders were present across all ADHD subtypes. Odds ratios (ORs) for twin concordance indicate genetic influence on severe inattentive (OR = 4.18; 95% confidence interval [CI], 1.52-11.53) and combined (OR = 5.25; 95% CI, 1.32-20.78) ADHD classes and ODD (OR = 1.49; 95% CI, 0.70-3.17), ODD/CD (OR = 3.32; 95% CI, 0.57-19.28), and ODD/CD/depression (OR = 1.20; 95% CI, 0.30-4.77) classes. Conclusions: Internalizing and externalizing disorders did not cluster differentially within ADHD subtypes. LCA may provide a more precise characterization of comorbidity with ADHD.